Effective method for simultaneous determination of abscisic acid, 3-indolacetic acid and gibberellic acid in commercial plant biostimulants by capillary electrophoresis with diode array detection - Chóez-Guaranda, Ivan (2024)
Phytohormones, also known as plant hormones, are naturally occurring chemical compounds that regulate various physiological processes in plants. In this work, a capillary electrophoretic coupled to a diode array detector (CE-DAD) method was developed and validated for the simultaneous quantification of abscisic acid (ABA), 3-indolacetic acid (IAA), and gibberellic acid (GA3) in commercial plant biostimulants. Sample preparation was carried out by liquid-liquid extraction using ethyl acetate. CE separation was performed in a fused-silica capillary and background electrolyte (BGE) consisting of borate buffer (50 mM, pH 9.3) applying a high voltage of 20 kV, a pressure of 50 mbar, and injection time of 35 s. The ABA, IAA, and GA3 were detected at 254, 220 and 195 nm respectively. The CE-DAD method validation results showed acceptable specificity, linearity, accuracy, and precision in the concentration range of 10-100 µg/mL for all compounds according to the (International Conference Harmonisation) ICH guidelines. The proposed method was satisfactory applied to the analysis of cited plant hormones in biostimulants and suggest that sample preparation is a reliable step for extraction of phytohormones containing carboxyl groups. Therefore, the developed and validated method could be implemented as a low-cost and fast analytical tool for quality control purposes.